Effect of Processing Parameters on the Properties of Rigid PVC/Organoclay Nanocomposites - Beg, M. D. H.; Zaman, Haydar U. (Oxford & I.B.H. Publishing Co. Pvt. Ltd, 2014)
In this study, PVC/organoclay nanocomposites were prepared by melt compounding PVC with three levels of organoclay loading (1, 3 and 5 wt%) at different screw rotating speeds, using plasticizer (dioctyl phthalate, DOP) with various contents (10, 20 and 30 wt%). Effects of screw rotating speed, organoclay loading and plasticizer content on mechanical and thermal properties of nanocomposites were investigated. TEM photographs showed that the organoclay was intercalated and partly exfoliated in the presence of DOP during melt mixing. The mechanical properties of nanocomposites improved with the addition of organoclay at the speed of 100 rpm. In addition, incorporation of DOP further increased the mechanical properties of the nanocomposites. Thermal properties of the nanocomposites were found to increase as a result of clay incorporation.